ANALISIS PENETAPAN HARGA POKOK PENJUALAN DALAM MENINGKATKAN LABA PADA CV. SINAR ABADI KENDARI - Kusman Paluala; Abd Azis Muthalib; Muh Nur (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2024)
The objective of this research was to understand and analyze the determination of the Cost of Goods Sold (COGS) by CV. Sinar Abadi Kendari; the calculation of profit obtained by the company; and the impact of the COGS on profit enhancement at CV. Sinar Abadi Kendari. This study falls under the category of descriptive quantitative research and utilized both primary and secondary data, including initial inventory data, purchasing data, final inventory data, sales data, and profit data for the period of January to December 2021 obtained from the company CV. Sinar Abadi Kendari, which is the subject of this research. The analytical tools used were quantitative descriptive analysis and correlation analysis using SPSS software. The results of the research, through quantitative descriptive analysis, indicated that the COGS determined by CV. Sinar Abadi Kendari effectively increased the company's profit. Furthermore, the correlation analysis revealed a significant influence of the COGS on profit, with a negative correlation direction. Thus, it was concluded that the COGS has a significant impact on profit. This study aims to examine the processes involved in determining the Cost of Goods Sold (COGS), computing profits, and the effect of COGS on profit enhancement at CV. Sinar Abadi Kendari. Adopting a descriptive quantitative approach, the study analyzes primary and secondary data ranging from initial and final inventory, purchases, sales, to company profits over the year 2021. Quantitative descriptive and correlation analyses were performed with the aid of SPSS software. Findings from the descriptive analysis confirm that COGS determination at CV. Sinar Abadi Kendari contributes to profit growth. Correlation analysis demonstrates a significant and negative relationship between COGS and profit, affirming the substantial effect of COGS on profit. The study concludes that COGS plays a crucial role in influencing profit margins and proposes that effective management of COGS is essential for enhancing company profitability.